Spatio-temporal constraints on lithospheric development in the southwest-central Yilgarn Craton, Western Australia - Mole, D.; Fiorentini, M.; Thebaud, N.; McCuaig, T.; Cassidy, K.; Kirkland, Chris; Wingate, M.; Romano, S.; Doublier, M.; Belousova, E. (2012)
The Archean western Yilgarn Craton contains an extensive record of supracrustal formation from ca 3730 to ca 2675 Ma, as well as evidence of an ensialic crustal component as old as ca 4400 Ma. These features make the western Yilgarn Craton one of the oldest crustal provinces on Earth and ideal for the study of Archean crustal evolution. Spatial analysis of new and collated U-Pb age data define three broad pulses of granite emplacement at ca 3000-2820, ca 2805-2720 and ca 2720-2600 Ma, with a period of regional quiescence at 2820-2805 Ma. Within these pulses, major peaks in granite production are defined at ca 2920, ca 2890, ca 2845, ca 2790, ca 2750, ca 2690, ca 2665, ca 2655, ca 2630, and ca 2615 Ma; with lesser inherited material as old as 3670 Ma. In the western Yilgarn Craton, all terranes show evidence of granite activity at ca 3000-2820 Ma. The South West Terrane and Southern Cross Domain share granite pulses at ca 2950-2920, 2880-2820 and 2800-2720 Ma, although during these intervals granite magmatism tends to dominate in one terrane, i.e. ca 2805-2780 Ma granite activity predominantly occurs in the South West Terrane, while 2780-2720 Ma activity is focused in the Southern Cross Domain. Including the period of quiescence, granite production is relatively minor between ca 2820 and ca 2720 Ma relative to the 3000-2820 Ma and 2720-2600 Ma intervals, suggesting limited crustal development at this time. This period corresponds with widespread greenstone formation throughout the western Yilgarn Craton.The major pulse of granite emplacement and crustal evolution occurs at ca 2700-2600 Ma, with the main phases of activity at ca 2680-2650 Ma in the Southern Cross Domain and ca 2640-2620 Ma in the South West Terrane. These pulses coincide with a craton-wide transition in granite geochemistry from high-Ca to low-Ca at ca 2650 Ma and suggest significant variations in the method and timing of melt generation. Results from this study provide new constraints on the spatio-temporal evolution of the lithosphere in the western Yilgarn Craton. The spatial distribution of these age data suggest that existing terrane boundaries should be revised with the South West Terrane separated into at least two distinct domains, and the boundary between the Youanmi and South West Terranes moved westward to correspond with the eastern extent of charnockite granites.